Kidney transplant graft outcomes in 379 257 recipients on 3 continents. Issue 8 (24th March 2018) - Merion, Robert M.; Goodrich, Nathan P.; Johnson, Rachel J.; McDonald, Stephen P.; Russ, Graeme R.; Gillespie, Brenda W.; Collett, David
Abstract : Kidney transplant outcomes that vary by program or geopolitical unit may result from variability in practice patterns or health care delivery systems. In this collaborative study, we compared kidney graft outcomes among 4 countries (United States, United Kingdom, Australia, and New Zealand) on 3 continents. We analyzed transplant and follow‐up registry data from 1988‐2014 for 379 257 recipients of first kidney‐only transplants using Cox regression. Compared to the United States, 1‐year adjusted graft failure risk was significantly higher in the United Kingdom (hazard ratio [HR] 1.22, 95% confidence interval [CI] 1.18‐1.26, P < .001) and New Zealand (hazard ratio [HR] 1.29, 95% confidence interval [CI] 1.14‐1.46, P < .001), but lower in Australia (HR 0.90, 95% CI 0.84‐0.96, P = .001). In contrast, long‐term adjusted graft failure risk (conditional on 1‐year function) was significantly higher in the United States compared to Australia, New Zealand, and the United Kingdom (HR 0.74, 0.75, and 0.74, respectively; each P < .001). Thus long‐term kidney graft outcomes are approximately 25% worse in the United States than in 3 other countries with well‐developed kidney transplant systems. Case mix differences and residual confounding from unmeasured factors were found to be unlikely explanations. These findings suggest that identification of potentially modifiable country‐specific differences in care delivery and/or practice patterns should be sought. Abstract : Comparisons of kidney transplant graft outcomes across four countries using registry data on transplants from 1988–2014 shows that long‐term adjusted graft failure risk is approximately 25% higher in the United States than in Australia, New Zealand, and the United Kingdom.